Microbial electro-fermentation for synthesis of chemicals and biofuels driven by bi-directional extracellular electron transfer - Gong, Ziying (Synth Syst Biotechnol, 2020)
Electroactive bacteria could perform bi-directional extracellular electron transfer (EET) to exchange electrons and energy with extracellular environments, thus playing a central role in microbial electro-fermentation (EF) process. Unbalanced fermentation and microbial electrosynthesis are the main pathways to produce value-added chemicals and biofuels. However, the low efficiency of the bi-directional EET is a dominating bottleneck in these processes. In this review, we firstly demonstrate the main bi-directional EET mechanisms during EF, including the direct EET and the shuttle-mediated EET. Then, we review representative milestones and progresses in unbalanced fermentation via anode outward EET and microbial electrosynthesis via inward EET based on these two EET mechanisms in detail. Furthermore, we summarize the main synthetic biology strategies in improving the bi-directional EET and target products synthesis, thus to enhance the efficiencies in unbalanced fermentation and microbial electrosynthesis. Lastly, a perspective on the applications of microbial electro-fermentation is provided.